Uniqueness of Rovaniemi as a travel destination : what factors make Rovaniemi unique as a tourism destination in comparison to Lapland from Finnish travelers’ perspective - Nurmela, Katariina (fi=Lapin yliopisto|en=University of Lapland|, 2024)
After the arrival of the Covid-19 pandemic in 2020, domestic tourism gained increasing prominence globally, including in Finland, prompting Rovaniemi's tourism industry to pivot towards domestic tourism. However, research on domestic tourism in Rovaniemi remains limited, with existing studies primarily focusing on international tourists or winter tourism, neglecting the unique dynamics of domestic tourism. This thesis aims to fill this research gap by examining Rovaniemi's attractiveness and uniqueness as a destination for Finnish people, investigating factors that distinguish it, its appeal to domestic tourists, and its differentiation from Lapland. Data was collected through a questionnaire administered by Kantar TNS through its respondent panel. Through a comprehensive analysis of various factors, including destination selection processes and domestic tourism trends, the study seeks to uncover the distinctive features that set Rovaniemi apart within the broader Lapland region. The findings reveal that Rovaniemi holds significant appeal for many Finnish individuals, driven by unique elements such as Santa Claus, the Arctic Circle, and different natural phenomena. Rovaniemi's strategic positioning and unique cultural and natural assets make it an interesting destination among Finnish travelers. The study highlights the importance of understanding Finnish people's perceptions and preferences to inform destination management and marketing strategies. It emphasizes the need for balanced tourism practices to preserve Rovaniemi's environment and culture while ensuring accessibility and affordability for visitors. This Master’s thesis concludes by identifying avenues for future research, including qualitative studies on destination uniqueness perceptions and exploration of emerging travel trends. Overall, the study provides valuable insights to enhance Rovaniemi's attractiveness as a tourism destination and promote its long-term success in Finland's tourism landscape.